Normalization of Citation Impact in Economics - Lutz Bornmann; Klaus Wohlrabe (Center for Economic Studies and ifo Institute (CESifo), 2017)
This study is intended to facilitate fair research evaluations in economics. Field- and time-normalization of citation impact is the standard method in bibliometrics. Since citation rates for journal papers differ substantially across publication years and Journal of Economic Literature (JEL) classification codes, citation rates should be normalized for the comparison of papers across different time periods and economic subfields. Without normalization, both factors that are independent of research quality bias the results of citation analyses. We introduce two normalized indicators in economics, which are the most important indicators in bibliometrics: (1) the mean normalized citation score (MNCS) compares the citation impact of a focal paper with the mean impact of similar papers published in the same economic subfield and publication year. (2) PPtop 50% is the share of papers that belong to the above-average half in a certain subfield and time period. Since the MNCS is based on arithmetic averages despite skewed citation distributions, we recommend using PPtop 50% for fair comparisons of entities in economics (e.g. researchers, institutions, or countries). In this study, we apply the method to 294 journals (including normalized scores for 192,524 papers) by assigning them to four citation impact classes and identifying 33 outstandingly cited economics journals.
Keywords: A11; A12; A14; 330; bibliometrics; citations; JEL codes; journal ranking; mean normalized citation score (MNCS); citation percentile; PPtop 50%